Відповідальність військовослужбовців за незаконне заволодіння зброєю, військовим майном та бойовими припасами за законодавством країн романо-германської правової сім’ї - Русанова, Л. В.; Rusanova, L. V. (Вісник Кримінологічної асоціації України. - 2017. - № 1 (15). - С. 207-221, 2017)
У статті розглянуто питання відповідальності військовослужбовців за викрадення, привласнення, вимагання зброї, військового майна та бойових припасів у країнах, які належать до романо-германської правової сім’ї. Приділено увагу особливостям військово-кримінального законодавства. Встановлено, що більшість держав, які належать до цієї сім’ї, у своїх нормативно-правових актах не містить окремих норм, аналогічних ст. 410 Кримінального кодексу України.

The author of the article has researched the issues of the liability of servicemen for the theft, misappropriation, extortion of weapons, military equipment and ammunition in the countries belonging to Romano-Germanic legal family, and has analyzed the law norms, according to which the servicemen of the armed forces of the leading countries are responsible for theft, misappropriation of weapons, military equipment, ammunition, etc. The issues of criminal liability of servicemen under the Art. 410 of the Criminal Code of Ukraine were the subject of research of such scholars as: V. P. Bodaievskyi, S. I. Diachuk, V. I. Kasyniuk, V. A. Klymenko, M. I. Korzhanskyi, M. I. Panov, M. I. Havroniuk, S. O. Kharytonov, O. A. Chuvakov, O. M. Sarnavskyi and others. Some aspects were studied by V. H. Kundeus, V. P. Tykhyi, Z. A. Trostiuk and international experience of misappropriation of military equipment at the level of chapters to textbooks of criminal law was studied by N. A. Holovanova, A. V. Savitskyi, M. M. Senko, V. V. Sydorin, M. I. Havroniuk, V. M. Chkhykvadze and others. Due to the familiarization with the normative and legal acts of different countries, it was found out that the military, military and criminal legislations of most countries in the world are in many ways similar, in particular, contains provisions that establish both the procedure of subordination and military service and performance of service duties in peacetime and wartime. However, despite the existence of common sources, the similarity of structure and historical path of formation and development of the law within Romano-Germanic legal family, which brings together the countries of Western Europe, two close to each other types of military criminal law – “Germanic” and “French” were formed, where the features of each of them were reflected in the structure and content of their specific sources. Thus, the peculiarity of sources of Roman type is the presence of the norms of both military and criminal, and criminal and procedural law. They are called the Codes of Military Justice in many countries of this group, where the number and scope of procedural norms is slightly smaller in number and volume of the norms of military and criminal law, and in some countries even exceed their bulk. The existence of an independent Military and Criminal Code with general and special parts, which consists of only with norms of substantive law regulating just military security criminal and legal relationships – is characteristic feature of the Germanic group. Besides, it has been found out that the nature of public danger of crimes involving misappropriation of munitions by servicemen with lucrative motives committed in peacetime and wartime is assessed differently in the European countries. Analysis of the Codes norms of the countries of Romano-Germanic legal family has demonstrated that these acts contain corpus delicti similar to the Criminal Code of Ukraine. However, in our country they are contained in a separate section (this is explained primarily by the fact that the Criminal Code of Ukraine was called as the only source of criminal law, the existence of other criminal laws, including those, which establish criminal liability of servicemen (as in the countries of Romano-Germanic legal family) is not allowed), while in the countries of Romano-Germanic legal family may be directly provided by the military and criminal law (France), and exist as specific norms in the military and criminal law, but refer to general and criminal norms (Germany, Norway) and finally, the liability of servicemen might occur under the general and criminal norms. It has been established that the inclusion of the norms of the military and criminal law into domestic criminal code, according to the legislator, assists to maximum forthcoming of the norms of general and military criminal law, implementing the principle of legality in the sphere of criminal and legal regulation of military relations.

В статье рассмотрены вопросы ответственности военнослужащих за незаконное завладение оружием, военным имуществом и боевыми припасами в странах, которые принадлежат к романо-германской правовой семье. Уделено внимание особенностям военно-уголовного законодательства. Выяснено, что государства, принадлежащие к этой семье, в своих уголовных кодексах не предусматривают норм, аналогичных ст. 410 Уголовного кодекса Украины.
Liability of servicemen for misappropriation of weapons, military equipment and ammunition under the legislation of the countries of romano-germanic legal family
Ответственность военнослужащих за незаконное завладение оружием, военным имуществом и боевыми припасами по законодательству стран романо-германской правовой семьи
Русанова, Л. В. Відповідальність військовослужбовців за незаконне заволодіння зброєю, військовим майном та бойовими припасами за законодавством країн романо-германської правової сім’ї / Людмила Василівна Русанова // Вісник Кримінологічної асоціації України. - 2017. - № 1 (15). - С. 207-221.
Rusanova, L. V. (2017), “Liability of servicemen for misappropriation of weapons, military equipment and ammunition under the legislation of the countries of Romano-Germanic legal family” [Vidpovidalnist viiskovosluzhbovtsiv za nezakonne zavolodinnia zbroieiu, viiskovym mainom ta boiovymy prypasamy za zakonodavstvom krain romano-hermanskoi pravovoi sim’i], Visnyk Kryminolohichnoi asotsiatsii Ukrainy, No. 1, pp. 207–221.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; правова сім’я; романо-германська правова сім’я; військово-кримінальне законодавство; романський тип; германський тип; військові злочини; викрадення зброї; викрадення; зброя; привласнення; вимагання; військове майно; бойові припаси; legal family; Romano-Germanic legal family; military and criminal legislation; Roman type; Germanic type; military crimes; theft; misappropriation; extortion; weapons; military equipment; ammunition; правовая семья; романо-германская правовая семья; военно-уголовное законодательство; военные преступления; романский тип; германский тип; хищение; присвоение; вымогательство